Numerical Methods - 3.3 Interpolation
DLMF | Formula | Constraints | Maple | Mathematica | Symbolic Maple |
Symbolic Mathematica |
Numeric Maple |
Numeric Mathematica |
---|---|---|---|---|---|---|---|---|
3.3#Ex3 | n_{0} = -\tfrac{1}{2}(n-\sigma) |
|
n[0] = -(1)/(2)*(n - sigma) |
Subscript[n, 0] == -Divide[1,2]*(n - \[Sigma]) |
Skipped - no semantic math | Skipped - no semantic math | - | - |
3.3#Ex4 | n_{1} = \tfrac{1}{2}(n+\sigma) |
|
n[1] = (1)/(2)*(n + sigma) |
Subscript[n, 1] == Divide[1,2]*(n + \[Sigma]) |
Skipped - no semantic math | Skipped - no semantic math | - | - |
3.3.E9 | \sigma = \tfrac{1}{2}(1-(-1)^{n}) |
|
sigma = (1)/(2)*(1 -(- 1)^(n)) |
\[Sigma] == Divide[1,2]*(1 -(- 1)^(n)) |
Skipped - no semantic math | Skipped - no semantic math | - | - |
3.3.E14 | f_{t} = (1-t)f_{0}+tf_{1}+R_{1,t} |
f[t] = (1 - t)*f[0]+ t*f[1]+ R[1 , t] |
Subscript[f, t] == (1 - t)*Subscript[f, 0]+ t*Subscript[f, 1]+ Subscript[R, 1 , t] |
Skipped - no semantic math | Skipped - no semantic math | - | - | |
3.3.E15 | c_{1} = \tfrac{1}{8} |
c[1] = (1)/(8) |
Subscript[c, 1] == Divide[1,8] |
Skipped - no semantic math | Skipped - no semantic math | - | - | |
3.3.E16 | f_{t} = \sum_{k=-1}^{1}A_{k}^{2}f_{k}+R_{2,t} |
f[t] = sum((A[k])^(2)*f[k], k = - 1..1)+ R[2 , t] |
Subscript[f, t] == Sum[(Subscript[A, k])^(2)*Subscript[f, k], {k, - 1, 1}, GenerateConditions->None]+ Subscript[R, 2 , t] |
Skipped - no semantic math | Skipped - no semantic math | - | - | |
3.3#Ex5 | A_{-1}^{2} = \tfrac{1}{2}t(t-1) |
|
(A[- 1])^(2) = (1)/(2)*t*(t - 1) |
(Subscript[A, - 1])^(2) == Divide[1,2]*t*(t - 1) |
Skipped - no semantic math | Skipped - no semantic math | - | - |
3.3#Ex6 | A_{0}^{2} = 1-t^{2} |
|
(A[0])^(2) = 1 - (t)^(2) |
(Subscript[A, 0])^(2) == 1 - (t)^(2) |
Skipped - no semantic math | Skipped - no semantic math | - | - |
3.3#Ex7 | A_{1}^{2} = \tfrac{1}{2}t(t+1) |
|
(A[1])^(2) = (1)/(2)*t*(t + 1) |
(Subscript[A, 1])^(2) == Divide[1,2]*t*(t + 1) |
Skipped - no semantic math | Skipped - no semantic math | - | - |
3.3.E18 | c_{2} = 1/(9\sqrt{3}) |
c[2] = 1/(9*sqrt(3)) |
Subscript[c, 2] == 1/(9*Sqrt[3]) |
Skipped - no semantic math | Skipped - no semantic math | - | - | |
3.3.E19 | f_{t} = \sum_{k=-1}^{2}A_{k}^{3}f_{k}+R_{3,t} |
f[t] = sum((A[k])^(3)*f[k], k = - 1..2)+ R[3 , t] |
Subscript[f, t] == Sum[(Subscript[A, k])^(3)*Subscript[f, k], {k, - 1, 2}, GenerateConditions->None]+ Subscript[R, 3 , t] |
Skipped - no semantic math | Skipped - no semantic math | - | - | |
3.3#Ex8 | A_{-1}^{3} = -\tfrac{1}{6}t(t-1)(t-2) |
|
(A[- 1])^(3) = -(1)/(6)*t*(t - 1)*(t - 2) |
(Subscript[A, - 1])^(3) == -Divide[1,6]*t*(t - 1)*(t - 2) |
Skipped - no semantic math | Skipped - no semantic math | - | - |
3.3#Ex9 | A_{0}^{3} = \tfrac{1}{2}(t^{2}-1)(t-2) |
|
(A[0])^(3) = (1)/(2)*((t)^(2)- 1)*(t - 2) |
(Subscript[A, 0])^(3) == Divide[1,2]*((t)^(2)- 1)*(t - 2) |
Skipped - no semantic math | Skipped - no semantic math | - | - |
3.3#Ex10 | A_{1}^{3} = -\tfrac{1}{2}t(t+1)(t-2) |
|
(A[1])^(3) = -(1)/(2)*t*(t + 1)*(t - 2) |
(Subscript[A, 1])^(3) == -Divide[1,2]*t*(t + 1)*(t - 2) |
Skipped - no semantic math | Skipped - no semantic math | - | - |
3.3#Ex11 | A_{2}^{3} = \tfrac{1}{6}t(t^{2}-1) |
|
(A[2])^(3) = (1)/(6)*t*((t)^(2)- 1) |
(Subscript[A, 2])^(3) == Divide[1,6]*t*((t)^(2)- 1) |
Skipped - no semantic math | Skipped - no semantic math | - | - |
3.3.E22 | f_{t} = \sum_{k=-2}^{2}A_{k}^{4}f_{k}+R_{4,t} |
f[t] = sum((A[k])^(4)*f[k], k = - 2..2)+ R[4 , t] |
Subscript[f, t] == Sum[(Subscript[A, k])^(4)*Subscript[f, k], {k, - 2, 2}, GenerateConditions->None]+ Subscript[R, 4 , t] |
Skipped - no semantic math | Skipped - no semantic math | - | - | |
3.3#Ex12 | A_{-2}^{4} = \tfrac{1}{24}t(t^{2}-1)(t-2) |
|
(A[- 2])^(4) = (1)/(24)*t*((t)^(2)- 1)*(t - 2) |
(Subscript[A, - 2])^(4) == Divide[1,24]*t*((t)^(2)- 1)*(t - 2) |
Skipped - no semantic math | Skipped - no semantic math | - | - |
3.3#Ex13 | A_{-1}^{4} = -\tfrac{1}{6}t(t-1)(t^{2}-4) |
|
(A[- 1])^(4) = -(1)/(6)*t*(t - 1)*((t)^(2)- 4) |
(Subscript[A, - 1])^(4) == -Divide[1,6]*t*(t - 1)*((t)^(2)- 4) |
Skipped - no semantic math | Skipped - no semantic math | - | - |
3.3#Ex14 | A_{0}^{4} = \tfrac{1}{4}(t^{2}-1)(t^{2}-4) |
|
(A[0])^(4) = (1)/(4)*((t)^(2)- 1)*((t)^(2)- 4) |
(Subscript[A, 0])^(4) == Divide[1,4]*((t)^(2)- 1)*((t)^(2)- 4) |
Skipped - no semantic math | Skipped - no semantic math | - | - |
3.3#Ex15 | A_{1}^{4} = -\tfrac{1}{6}t(t+1)(t^{2}-4) |
|
(A[1])^(4) = -(1)/(6)*t*(t + 1)*((t)^(2)- 4) |
(Subscript[A, 1])^(4) == -Divide[1,6]*t*(t + 1)*((t)^(2)- 4) |
Skipped - no semantic math | Skipped - no semantic math | - | - |
3.3#Ex16 | A_{2}^{4} = \tfrac{1}{24}t(t^{2}-1)(t+2) |
|
(A[2])^(4) = (1)/(24)*t*((t)^(2)- 1)*(t + 2) |
(Subscript[A, 2])^(4) == Divide[1,24]*t*((t)^(2)- 1)*(t + 2) |
Skipped - no semantic math | Skipped - no semantic math | - | - |
3.3.E25 | f_{t} = \sum_{k=-2}^{3}A_{k}^{5}f_{k}+R_{5,t} |
f[t] = sum((A[k])^(5)*f[k], k = - 2..3)+ R[5 , t] |
Subscript[f, t] == Sum[(Subscript[A, k])^(5)*Subscript[f, k], {k, - 2, 3}, GenerateConditions->None]+ Subscript[R, 5 , t] |
Skipped - no semantic math | Skipped - no semantic math | - | - | |
3.3#Ex17 | A_{-2}^{5} = -\tfrac{1}{120}t(t^{2}-1)(t-2)(t-3) |
|
(A[- 2])^(5) = -(1)/(120)*t*((t)^(2)- 1)*(t - 2)*(t - 3) |
(Subscript[A, - 2])^(5) == -Divide[1,120]*t*((t)^(2)- 1)*(t - 2)*(t - 3) |
Skipped - no semantic math | Skipped - no semantic math | - | - |
3.3#Ex18 | A_{-1}^{5} = \tfrac{1}{24}t(t-1)(t^{2}-4)(t-3) |
|
(A[- 1])^(5) = (1)/(24)*t*(t - 1)*((t)^(2)- 4)*(t - 3) |
(Subscript[A, - 1])^(5) == Divide[1,24]*t*(t - 1)*((t)^(2)- 4)*(t - 3) |
Skipped - no semantic math | Skipped - no semantic math | - | - |
3.3#Ex19 | A_{0}^{5} = -\tfrac{1}{12}(t^{2}-1)(t^{2}-4)(t-3) |
|
(A[0])^(5) = -(1)/(12)*((t)^(2)- 1)*((t)^(2)- 4)*(t - 3) |
(Subscript[A, 0])^(5) == -Divide[1,12]*((t)^(2)- 1)*((t)^(2)- 4)*(t - 3) |
Skipped - no semantic math | Skipped - no semantic math | - | - |
3.3#Ex20 | A_{1}^{5} = \tfrac{1}{12}t(t+1)(t^{2}-4)(t-3) |
|
(A[1])^(5) = (1)/(12)*t*(t + 1)*((t)^(2)- 4)*(t - 3) |
(Subscript[A, 1])^(5) == Divide[1,12]*t*(t + 1)*((t)^(2)- 4)*(t - 3) |
Skipped - no semantic math | Skipped - no semantic math | - | - |
3.3#Ex21 | A_{2}^{5} = -\tfrac{1}{24}t(t^{2}-1)(t+2)(t-3) |
|
(A[2])^(5) = -(1)/(24)*t*((t)^(2)- 1)*(t + 2)*(t - 3) |
(Subscript[A, 2])^(5) == -Divide[1,24]*t*((t)^(2)- 1)*(t + 2)*(t - 3) |
Skipped - no semantic math | Skipped - no semantic math | - | - |
3.3#Ex22 | A_{3}^{5} = \tfrac{1}{120}t(t^{2}-1)(t^{2}-4) |
|
(A[3])^(5) = (1)/(120)*t*((t)^(2)- 1)*((t)^(2)- 4) |
(Subscript[A, 3])^(5) == Divide[1,120]*t*((t)^(2)- 1)*((t)^(2)- 4) |
Skipped - no semantic math | Skipped - no semantic math | - | - |
3.3.E28 | f_{t} = \sum_{k=-3}^{3}A_{k}^{6}f_{k}+R_{6,t} |
f[t] = sum((A[k])^(6)*f[k], k = - 3..3)+ R[6 , t] |
Subscript[f, t] == Sum[(Subscript[A, k])^(6)*Subscript[f, k], {k, - 3, 3}, GenerateConditions->None]+ Subscript[R, 6 , t] |
Skipped - no semantic math | Skipped - no semantic math | - | - | |
3.3#Ex23 | A_{-3}^{6} = \tfrac{1}{720}t(t^{2}-1)(t-3)(t^{2}-4) |
|
(A[- 3])^(6) = (1)/(720)*t*((t)^(2)- 1)*(t - 3)*((t)^(2)- 4) |
(Subscript[A, - 3])^(6) == Divide[1,720]*t*((t)^(2)- 1)*(t - 3)*((t)^(2)- 4) |
Skipped - no semantic math | Skipped - no semantic math | - | - |
3.3#Ex24 | A_{-2}^{6} = -\tfrac{1}{120}t(t^{2}-1)(t-2)(t^{2}-9) |
|
(A[- 2])^(6) = -(1)/(120)*t*((t)^(2)- 1)*(t - 2)*((t)^(2)- 9) |
(Subscript[A, - 2])^(6) == -Divide[1,120]*t*((t)^(2)- 1)*(t - 2)*((t)^(2)- 9) |
Skipped - no semantic math | Skipped - no semantic math | - | - |
3.3#Ex25 | A_{-1}^{6} = \tfrac{1}{48}t(t-1)(t^{2}-4)(t^{2}-9) |
|
(A[- 1])^(6) = (1)/(48)*t*(t - 1)*((t)^(2)- 4)*((t)^(2)- 9) |
(Subscript[A, - 1])^(6) == Divide[1,48]*t*(t - 1)*((t)^(2)- 4)*((t)^(2)- 9) |
Skipped - no semantic math | Skipped - no semantic math | - | - |
3.3#Ex26 | A_{0}^{6} = -\tfrac{1}{36}(t^{2}-1)(t^{2}-4)(t^{2}-9) |
|
(A[0])^(6) = -(1)/(36)*((t)^(2)- 1)*((t)^(2)- 4)*((t)^(2)- 9) |
(Subscript[A, 0])^(6) == -Divide[1,36]*((t)^(2)- 1)*((t)^(2)- 4)*((t)^(2)- 9) |
Skipped - no semantic math | Skipped - no semantic math | - | - |
3.3#Ex27 | A_{1}^{6} = \tfrac{1}{48}t(t+1)(t^{2}-4)(t^{2}-9) |
|
(A[1])^(6) = (1)/(48)*t*(t + 1)*((t)^(2)- 4)*((t)^(2)- 9) |
(Subscript[A, 1])^(6) == Divide[1,48]*t*(t + 1)*((t)^(2)- 4)*((t)^(2)- 9) |
Skipped - no semantic math | Skipped - no semantic math | - | - |
3.3#Ex28 | A_{2}^{6} = -\tfrac{1}{120}t(t^{2}-1)(t+2)(t^{2}-9) |
|
(A[2])^(6) = -(1)/(120)*t*((t)^(2)- 1)*(t + 2)*((t)^(2)- 9) |
(Subscript[A, 2])^(6) == -Divide[1,120]*t*((t)^(2)- 1)*(t + 2)*((t)^(2)- 9) |
Skipped - no semantic math | Skipped - no semantic math | - | - |
3.3#Ex29 | A_{3}^{6} = \tfrac{1}{720}t(t^{2}-1)(t+3)(t^{2}-4) |
|
(A[3])^(6) = (1)/(720)*t*((t)^(2)- 1)*(t + 3)*((t)^(2)- 4) |
(Subscript[A, 3])^(6) == Divide[1,720]*t*((t)^(2)- 1)*(t + 3)*((t)^(2)- 4) |
Skipped - no semantic math | Skipped - no semantic math | - | - |
3.3.E31 | f_{t} = \sum_{k=-3}^{4}A_{k}^{7}f_{k}+R_{7,t} |
f[t] = sum((A[k])^(7)*f[k], k = - 3..4)+ R[7 , t] |
Subscript[f, t] == Sum[(Subscript[A, k])^(7)*Subscript[f, k], {k, - 3, 4}, GenerateConditions->None]+ Subscript[R, 7 , t] |
Skipped - no semantic math | Skipped - no semantic math | - | - | |
3.3#Ex30 | A_{-3}^{7} = -\tfrac{1}{5040}t(t^{2}-1)(t-3)(t-4)(t^{2}-4) |
|
(A[- 3])^(7) = -(1)/(5040)*t*((t)^(2)- 1)*(t - 3)*(t - 4)*((t)^(2)- 4) |
(Subscript[A, - 3])^(7) == -Divide[1,5040]*t*((t)^(2)- 1)*(t - 3)*(t - 4)*((t)^(2)- 4) |
Skipped - no semantic math | Skipped - no semantic math | - | - |
3.3#Ex31 | A_{-2}^{7} = \tfrac{1}{720}t(t^{2}-1)(t-2)(t-4)(t^{2}-9) |
|
(A[- 2])^(7) = (1)/(720)*t*((t)^(2)- 1)*(t - 2)*(t - 4)*((t)^(2)- 9) |
(Subscript[A, - 2])^(7) == Divide[1,720]*t*((t)^(2)- 1)*(t - 2)*(t - 4)*((t)^(2)- 9) |
Skipped - no semantic math | Skipped - no semantic math | - | - |
3.3#Ex32 | A_{-1}^{7} = -\tfrac{1}{240}t(t-1)(t-4)(t^{2}-4)(t^{2}-9) |
|
(A[- 1])^(7) = -(1)/(240)*t*(t - 1)*(t - 4)*((t)^(2)- 4)*((t)^(2)- 9) |
(Subscript[A, - 1])^(7) == -Divide[1,240]*t*(t - 1)*(t - 4)*((t)^(2)- 4)*((t)^(2)- 9) |
Skipped - no semantic math | Skipped - no semantic math | - | - |
3.3#Ex33 | A_{0}^{7} = \tfrac{1}{144}(t^{2}-1)(t-4)(t^{2}-4)(t^{2}-9) |
|
(A[0])^(7) = (1)/(144)*((t)^(2)- 1)*(t - 4)*((t)^(2)- 4)*((t)^(2)- 9) |
(Subscript[A, 0])^(7) == Divide[1,144]*((t)^(2)- 1)*(t - 4)*((t)^(2)- 4)*((t)^(2)- 9) |
Skipped - no semantic math | Skipped - no semantic math | - | - |
3.3#Ex34 | A_{1}^{7} = -\tfrac{1}{144}t(t+1)(t-4)(t^{2}-4)(t^{2}-9) |
|
(A[1])^(7) = -(1)/(144)*t*(t + 1)*(t - 4)*((t)^(2)- 4)*((t)^(2)- 9) |
(Subscript[A, 1])^(7) == -Divide[1,144]*t*(t + 1)*(t - 4)*((t)^(2)- 4)*((t)^(2)- 9) |
Skipped - no semantic math | Skipped - no semantic math | - | - |
3.3#Ex35 | A_{2}^{7} = \tfrac{1}{240}t(t^{2}-1)(t+2)(t-4)(t^{2}-9) |
|
(A[2])^(7) = (1)/(240)*t*((t)^(2)- 1)*(t + 2)*(t - 4)*((t)^(2)- 9) |
(Subscript[A, 2])^(7) == Divide[1,240]*t*((t)^(2)- 1)*(t + 2)*(t - 4)*((t)^(2)- 9) |
Skipped - no semantic math | Skipped - no semantic math | - | - |
3.3#Ex36 | A_{3}^{7} = -\tfrac{1}{720}t(t^{2}-1)(t+3)(t-4)(t^{2}-4) |
|
(A[3])^(7) = -(1)/(720)*t*((t)^(2)- 1)*(t + 3)*(t - 4)*((t)^(2)- 4) |
(Subscript[A, 3])^(7) == -Divide[1,720]*t*((t)^(2)- 1)*(t + 3)*(t - 4)*((t)^(2)- 4) |
Skipped - no semantic math | Skipped - no semantic math | - | - |
3.3#Ex37 | A_{4}^{7} = \tfrac{1}{5040}t(t^{2}-1)(t^{2}-4)(t^{2}-9) |
|
(A[4])^(7) = (1)/(5040)*t*((t)^(2)- 1)*((t)^(2)- 4)*((t)^(2)- 9) |
(Subscript[A, 4])^(7) == Divide[1,5040]*t*((t)^(2)- 1)*((t)^(2)- 4)*((t)^(2)- 9) |
Skipped - no semantic math | Skipped - no semantic math | - | - |
3.3#Ex38 | f = f_{0} |
|
f = f[0] |
f == Subscript[f, 0] |
Skipped - no semantic math | Skipped - no semantic math | - | - |
3.3#Ex39 | f = ({[z_{1}]}f-{[z_{0}]}f)/(z_{1}-z_{0}) |
|
f = ((z[1])*f -(z[0])*f)/(z[1]- z[0]) |
f == ((Subscript[z, 1])*f -(Subscript[z, 0])*f)/(Subscript[z, 1]- Subscript[z, 0]) |
Skipped - no semantic math | Skipped - no semantic math | - | - |
3.3#Ex40 | f = ({[z_{1},z_{2}]}f-{[z_{0},z_{1}]}f)/(z_{2}-z_{0}) |
|
f = ([z[1], z[2]]*f -[z[0], z[1]]*f)/(z[2]- z[0]) |
f == ([Subscript[z, 1], Subscript[z, 2]]*f -[Subscript[z, 0], Subscript[z, 1]]*f)/(Subscript[z, 2]- Subscript[z, 0]) |
Skipped - no semantic math | Skipped - no semantic math | - | - |
3.3.E39 | x(f) = [f_{0}]x+(f-f_{0})[f_{0},f_{1}]x+(f-f_{0})(f-f_{1})[f_{0},f_{1},f_{2}]x |
|
x(f) = (f[0])*x(+)*(f - f[0])*[f[0], f[1]]*x(+)*(f - f[0])*(f - f[1])*[f[0], f[1], f[2]]*x |
x[f] == (Subscript[f, 0])*x[+]*(f - Subscript[f, 0])*[Subscript[f, 0], Subscript[f, 1]]*x[+]*(f - Subscript[f, 0])*(f - Subscript[f, 1])*[Subscript[f, 0], Subscript[f, 1], Subscript[f, 2]]*x |
Skipped - no semantic math | Skipped - no semantic math | - | - |
3.3.E40 | x = -2.2+1.44011\;1973(f-0.09614\;53780)+0.08865\;85832\*(f-0.09614\;53780)(f-0.02670\;63331) |
|
x = - 2.2 + 1.440111973*(f - 0.0961453780)+ 0.0886585832 *(f - 0.0961453780)*(f - 0.0267063331) |
x == - 2.2 + 1.440111973*(f - 0.0961453780)+ 0.0886585832 *(f - 0.0961453780)*(f - 0.0267063331) |
Skipped - no semantic math | Skipped - no semantic math | - | - |